(untitled) (Journal of Medical & Health Sciences Review, 2025)
Iron oxide nanoparticles represent a promising platform for targeted cancer therapy due to their unique magnetic properties, biocompatibility, and potential for surface functionalization. This study synthesized IONPs via the co-precipitation method and conducted a comprehensive physicochemical and biological characterization to evaluate their theranostic potential. The nanoparticles were characterized using UV-Vis spectroscopy, FTIR, XRD, TEM, and DLS, confirming the successful formation of crystalline magnetite with a spherical morphology and an average size of 10–25 nm, albeit with some aggregation in suspension. Biological assessments demonstrated a dose-dependent cytotoxicity in HeLa cancer cells while maintaining high viability in normal fibroblast cells, indicating selective toxicity. Doxorubicin was effectively loaded (72% efficiency) and exhibited a pH-responsive release profile, with significantly accelerated release under acidic conditions (pH 5.0) mimicking the tumor microenvironment. Cellular uptake studies confirmed the efficient internalization of nanoparticles into HeLa cells. The results collectively establish these synthesized Iron oxide nanoparticles as effective, biocompatible, and magnetically guidable nanocarriers, bridging the critical gap between material design and biological performance for advanced targeted cancer therapy.